Comparative evaluation of commercial Douchi by different molds: Biogenic amines, non-volatile and volatile compounds - Aijun Li; Gang Yang; Zhirong Wang; Shenglan Liao; Muying Du; Jun Song; Jianquan Kan (Food Science and Human Wellness)
To provide new insights into the development and utilization of Douchi artificial starters, three common strains (Aspergillus oryzae, Mucor racemosus, and Rhizopus oligosporus) were used to study their influence on the fermentation of Douchi. The results showed that the biogenic amine contents of the three types of Douchi were all within the safe range and far lower than those of traditional fermented Douchi. Aspergillus-type Douchi produced more free amino acids than the other two types of Douchi, and its umami taste was more prominent in sensory evaluation (P < 0.01), while Mucor-type and Rhizopus-type Douchi produced more esters and pyrazines, making the aroma, sauce, and Douchi flavor more abundant. According to the Pearson and PLS analyses results, sweetness was significantly negatively correlated with phenylalanine, cysteine, and acetic acid (P < 0.05), bitterness was significantly negatively correlated with malic acid (P < 0.05), the sour taste was significantly positively correlated with citric acid and most free amino acids (P < 0.05), while astringency was significantly negatively correlated with glucose (P < 0.001). Thirteen volatile compounds such as furfuryl alcohol, phenethyl alcohol, and benzaldehyde caused the flavor difference of three types of Douchi. This study provides theoretical basis for the selection of starting strains for commercial Douchi production.